Integrated widely targeted metabolomics and network pharmacology revealed quality disparities between Guizhou and conventional producing areas of Codonopsis Radix - Zhang, Kaixian; Zhang, Delin; Yang, Qingfang; Long, Langtao; Xie, Jian; Wang, Yong; Yao, Qiuyang; Wu, Faming; Liu, Sha (Frontiers in Nutrition, 2023)
Introduction: With the internationalization of traditional Chinese medicine, the demand for medicinal and edible Codonopsis Radix (CR) is increasing, and its medicinal resources have attracted attention. CR is a famous traditional Chinese medicine with a long pharmaceutical and edible history. Guizhou has abundant CR resources, but in the absence of systematic studies on species identification and chemical compositions, it has not been fully utilized. Methodology: Plant morphology and DNA barcoding techniques were used to identify LD and WD species. Widely targeted metabolomics and network pharmacology were utilized to explore metabolite differences between LD and WD, as well as the three Chinese Pharmacopoeia CRs, and to predict pharmacological mechanisms of action for the dominant differential metabolites. Revealing the material basis of the excellent food properties of both. Results: The results of plant traits and DNA barcoding molecular identification indicated that Luodang (LD) and Weidang (WD) from Guizhou were Codonopsis tangshen, C. pilosula., respectively. Widely targeted metabolomics analysis revealed that a total of 1116 metabolites from 14 categories, including phenolic acids, lipids, flavonoids, etc., were found in the five CRs, shared 1054 (94.4%) metabolites. LD and WD each contained 3 and 10 dominant differential metabolites, respectively, which were primarily flavonoids and amino acids. Amino acids, phenolic acids, and organic acids play important roles in the excellent food attributes of them. In CR, 8 dominant differential metabolites were discovered for the first time, including isoorientin-7-O-(6′′-feruloyl) glucoside, N-formyl-L-methionine, and cyclo (Phe-Glu), etc. Network pharmacology analyses showed that LD dominant differential metabolites were closely related to anti-tumor, cardiovascular disease improvement, nervous system protection, and metabolic disease treatment, whereas WD was closely related to nervous system protection and cardiovascular disease improvement. Conclusion: The species of LD and WD were included in the Chinese Pharmacopoeia, and their metabolite profiles were remarkably similar to CR from traditional producing areas. Therefore, LD and WD can be used and promoted medicinally as CR and have potential value for new drug development. This work enriched the database of CR compounds and provided a reference for quality control, resource development, and new drug development of CR.